CXCR3 AND CCR5 ARE BOTH REQUIRED FOR T CELL MEDIATED PROTECTION AGAINST C. TRACHOMATIS INFECTION IN THE MURINE GENITAL MUCOSA - Olive, Andrew J. (2010)
Chemokine receptors direct T lymphocytes to the site of an infection by following coordinated chemokine gradients, which allow their recruitment to specific tissues. Although identification of receptors needed for homing to some mucosal sites, such as skin and gut, have been elucidated, the receptors that direct lymphocytes to the genital mucosa remain relatively uncharacterized. Here we identify that the chemokine receptors CXCR3 and CCR5 are pivotal for T lymphocyte access to the genital tract during Chlamydia trachomatis infection. Chlamydia specific CD4(+) transgenic T cells that lack CXCR3 or CCR5 do not accumulate in the genital mucosa following infection. Loss of either CXCR3 or CCR5 impairs the protective capacity of Chlamydia specific T cells, while T cells lacking both receptors are completely non-protective. These results show that CXCR3 and CCR5 are the predominant chemokine receptors, which act cooperatively to promote homing to the genital mucosa during Chlamydia infection.